Tren Keberhasilan Mediasi di Pengadilan Agama Wilayah Madura dan Faktor-faktor yang Memengaruhinya - Ach Rois; Galuh Widitya Qomaro (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This research aims to analyze the success of mediation in the Madura Regional Religious Court. This research uses a qualitative method with a field approach where data is obtained from interviews with judges, mediators and parties involved in the mediation process at the Madura Regional Religious Court. The research results show that the Sumenep and Pamekasan District Religious Courts have a higher number of cases that are successful through mediation compared to Sampang and Bangkalan Districts. The failure factor for mediation in Religious Courts throughout the island of Madura is that the Madurese people still do not fully understand the mediation system, plaintiffs and defendants tend to rely on advocates. The trend of successful mediation in the Madura Regional Religious Court is less than half of the divorce cases submitted to the Religious Court.